SISTEM INFORMASI GEOGRAFIS SUMBER DAYA ALAM INDONESIA BERBASIS WEB - Tiara, Shindy (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
Geographical information system is a technology for managing, analyzing and disseminating geographic information related to spatial layout and related information. With regard to natural resources, geographic information will contain the location of an area, and information about natural resources contained in the area. Changes that occur at any time in nature related to adding or subtracting data can be done up to date without having to create new ones. In building a geographic information system of Indonesia's natural resources, Indonesia uses Mapserver as a mapping server and PHP script as a web programming language in building web pages. The research was conducted in four stages, namely the Preparation, Design, Implementation, and Trial stages. The result of this research is that geographic information system that displays digital maps can be stored in the form of shape files that can be created using a desktop-based information system software, namely ArcView. In addition, the geographic information system of natural resources can be used as a source of information regarding the distribution of Indonesia's natural resources which can be accessed by the wider community both from within and outside the country.